2020
DOI: 10.3390/rs12081305
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Mapping and Monitoring Using Persistent Scatterer Interferometry (PSI) Technique in the French Alps

Abstract: Continuous geodetic measurements in landslide prone regions are necessary to avoid disasters and better understand the spatiotemporal and kinematic evolution of landslides. The detection and characterization of landslides in high alpine environments remains a challenge associated with difficult accessibility, extensive coverage, limitations of available techniques, and the complex nature of landslide process. Recent studies using space-based observations and especially Persistent Scatterer Interferometry (PSI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 71 publications
4
69
0
Order By: Relevance
“…This is similar to the resolution of other landslide products generated for emergency response (e.g. Bessette-Kirton et al, 2019;Nowicki Jessee et al, 2018)…”
Section: Data Processingsupporting
confidence: 79%
See 2 more Smart Citations
“…This is similar to the resolution of other landslide products generated for emergency response (e.g. Bessette-Kirton et al, 2019;Nowicki Jessee et al, 2018)…”
Section: Data Processingsupporting
confidence: 79%
“…The aggregated resolution of 200 m × 220 m that we used here was not high enough to identify individual landslides. However it was higher than the resolution of most empirical landslide susceptibility models designed for rapid response (Allstadt et al, 2018;Nowicki Jessee et al, 2018) and landslide maps generated from optical satellite imagery for use in aid efforts by Bessette-Kirton et al (2019) following Hurricane Maria, Puerto Rico, in 2017 and by Williams et al (2018) following the 2015 Gorkha earthquake. SAR data seem best suited to producing products at this spatial scale.…”
Section: Landslide Density Estimationmentioning
confidence: 96%
See 1 more Smart Citation
“…Since the initial development of spaceborne synthetic aperture radar (SAR) systems and the demonstration of the SAR interferometric capability, the technique has reached its maturity for the detection of earthquake-induced ground displacements (Cornou et al 2020;Bacques et al 2020), among other geohazards (Delgado Blasco et al 2019;Papageorgiou et al 2019;Aslan et al 2020;Cigna and Tapete 2020;Vassilakis et al 2020). In the last decade, Earth Observation (EO) satellite missions are providing a richness of data at improved spatial resolution and coverage, as well as reduced revisit time, while the latest generation of SAR sensors ensures the millimeter precision of interferometric measurements (Gisinger et al 2019).…”
Section: Spaceborne Imaging Geodesymentioning
confidence: 99%
“…Approaches for the automatic detection of such irregular patterns in space and time have been developed already (Zhu et al, 2018), few also considering the interaction between geology and observed subsidence (Pratesi et el., 2016;North et al, 2017). While some approaches rely principally on the velocity estimates for clustering (Kalia, 2018;Aslan, 2020), other approaches consider the time series of the displacements for identifying different deformation regimes (Zhu et al, 2018). This information is particularly important for infrastructure analysis, as many factors may impact the deformation (e.g.…”
Section: State-of-the-artmentioning
confidence: 99%